Identification of Quorum Sensing Activators and Inhibitors in The Marine Sponge Sarcotragus spinosulus - Saurav, Kumar; Borbone, Nicola; Burgsdorf, Ilia; Teta, Roberta; Caso, Alessia; Bar-Shalom, Rinat; Esposito, Germana; Britstein, Maya; Steindler, Laura; Costantino, Valeria (Marine drugs, 2020)
Marine sponges, a well-documented prolific source of natural products, harbor highly diverse microbial communities. Their extracts were previously shown to contain quorum sensing (QS) signal molecules of the N-acyl homoserine lactone (AHL) type, known to orchestrate bacterial gene regulation. Some bacteria and eukaryotic organisms are known to produce molecules that can interfere with QS signaling, thus affecting microbial genetic regulation and function. In the present study, we established the production of both QS signal molecules as well as QS inhibitory (QSI) molecules in the sponge species Sarcotragus spinosulus. A total of eighteen saturated acyl chain AHLs were identified along with six unsaturated acyl chain AHLs. Bioassay-guided purification led to the isolation of two brominated metabolites with QSI activity. The structures of these compounds were elucidated by comparative spectral analysis of 1HNMR and HR-MS data and were identified as 3-bromo-4-methoxyphenethylamine (1) and 5,6-dibromo-N,N-dimethyltryptamine (2). The QSI activity of compounds 1 and 2 was evaluated using reporter gene assays for long- and short-chain AHL signals (Escherichia coli pSB1075 and E. coli pSB401, respectively). QSI activity was further confirmed by measuring dose-dependent inhibition of proteolytic activity and pyocyanin production in Pseudomonas aeruginosa PAO1. The obtained results show the coexistence of QS and QSI in S. spinosulus, a complex signal network that may mediate the orchestrated function of the microbiome within the sponge holobiont.
Keywords: Animals; pyokyanin; Virulence Factors; luminiscenční měření; N-acyl homoserine lactone; Escherichia coli; quorum sensing; Porifera; Pyocyanine; Quorum Sensing; proteasy; Phylogeny; sponge; Peptide Hydrolases; 3-bromo-4-methoxyphenethylamine; Sarcotragus spinosulus; zvířata; fylogeneze; 5,6-dibromo-N,N-dimethyltryptamine; Luminescent Measurements; faktory virulence; quorum sensing inhibition